Victim age and capital sentencing outcomes in North Carolina (1977–2009) - Marier, Christopher J. (Criminal justice studies, 2018)
Age is prominent among theories of criminology and victimology. It is less conspicuous in punishment theory, despite its emphasis in retributive theory and lawmaking. The present study evaluated competing ‘years of life lost’ and ‘vulnerable victim’ hypotheses to examine the influence of victim age in capital sentencing decisions. Using case file data on the population of capital murder trials in the State of North Carolina (1977-2009), our findings produce mixed results. Our quantitative analyses suggest that death sentences are significantly less likely in direct proportion to victim age. Killers of elderly victims are less likely to receive the death penalty; conversely, the odds of a death sentences are slightly greater for killers of child victims. Supplementary qualitative analyses suggest that while many child and elderly victims were not per se ‘vulnerable,’ a substantial subset of each clearly were treated as such. We discuss implications for vulnerable victim research and the role of quasi-legal factors in case outcomes.